The Role of Credit Facilities and Micro and Small Enterprises (MSEs) in Enhancing Rural Development Performance (A Study in Villages in Central Sulawesi Province) - Defrina Sarapung, Seren; Chairil Furqan, Andi; Zahra, Femilia; ., Megawati (KnE Social Sciences, 2024)
This research aims to analyze the extent to which the presence and role of credit facilities and micro and small enterprises (MSEs) in rural areas contribute to village development, especially in achieving the Village Development Index (VDI), which comprises three dimensions: the Social Resilience Index (SRI), Economic Resilience Index (ERI), and Environmental Resilience Index (EnRI). This study uses a quantitative method and cross-sectional data from 1842 villages in the Central Sulawesi Province sourced from the 2021 village potential data provided by the Central Statistics Agency, with a final sample of 1783 observations. The results indicate that the presence of both credit facilities and MSEs in rural areas has contributed to the achievement of VDI. Additionally, it was found that the presence of MSEs can mediate the influence of credit facilities on VDI. The existence of credit facilities in rural areas encourages the increase of MSEs in those areas, which in turn contributes to the improvement of VDI. The findings imply that for the strategy of accelerating rural development in Indonesia, the government, regional governments, financial institutions (banks and non-banks) and other stakeholders need to establish policies to enhance collaboration and innovative programs for the empowerment of village communities, including the provision of accessible, affordable, and reachable credit facilities for rural communities. The existence of such programs is expected to stimulate an increase in the number of MSEs and enhance economic activities in rural areas. This will then lead to an improvement in VDI. Keywords: credit facilities, micro and small enterprises, rural development, village development index